Method for preparing composite polyester by using carbon dots and polyester

By blending carbon dots with polyester or in-situ polymerization, composite polyester with excellent mechanical properties and fluorescence is prepared, which solves the performance loss problem of polyester materials in the prior art when improving elastic modulus and molding performance, and achieves efficient flame retardant and thermal stability improvement.

CN115181398BActive Publication Date: 2025-04-01BEIJING INST OF CLOTHING TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110363006.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-04-02
Publication Date
2025-04-01
Estimated Expiration
2041-04-02

AI Technical Summary

Technical Problem

In the process of improving the elastic modulus and forming properties of existing polyester materials often lose other properties, such as heat resistance and mechanical properties, and nanocarbon materials are prone to agglomeration during the addition process, resulting in no significant improvement in mechanical properties, which is relatively high.

Method used

The method of blending carbon dots with polyester or in-situ polymerization is adopted. The carbon dots are used as crosslinking points to improve the mechanical properties and fluorescence of the composite polyester. Carbon dots with small particle size are prepared by hydrothermal method, and composite polyesters are prepared with alcohol compounds and carboxylic acid compounds.

Benefits of technology

The mechanical properties and fluorescence properties of the composite polyester are improved, the thermal weight loss rate is reduced, the heat insulation carbon layer is formed, and the flame retardant and crystallization properties of the material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present invention discloses a composite polyester prepared by carbon dots and polyester. The doping of carbon dots gives the polyester excellent mechanical properties and fluorescence, and has the potential to prepare fluorescent anti-counterfeiting fibers. The present invention adopts a blending or in-situ polymerization method to prepare the composite polyester. The carbon dots are used as crosslinking points in the polymerization system, so that the residual carbon content of the system is increased and the thermal weight loss rate is reduced. Since the carbon dots are highly compatible with polyester, they are conducive to improving the mechanical properties of the matrix polyester, providing a new development idea for the polyester enhancement modification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer composite materials, and particularly relates to a method for preparing composite polyester by using carbon dots in coordination with polyester. Background Art

[0002] Polyester is the most widely used and consumed polymer material. As the earliest linear thermoplastic polymer to achieve industrial application, it has been widely used in plastic packaging, film and chemical fiber fields due to its excellent physical and mechanical properties such as high modulus, high strength and high elasticity. The application of polyester materials in the fields of automobiles, industrial and civil construction, household goods, electronic appliances, etc. has brought convenience to people's lives. However, since its oxygen index is generally only 21% to 22%, it is a fusible and flammable fiber, which brings potential unsafe factors to people's lives and property.

[0003] Polyester is represented by polyethylene terephthalate (PET). PET has ester bonds and will decompose under the action of strong acid, strong alkali and water vapor. It is resistant to organic solvents and has good weather resistance. The disadvantages are slow crystallization rate, difficult molding, high molding temperature, long production cycle and poor impact resistance.

[0004] In the prior art, improving the elastic modulus or elongation at break of polyester, or giving polyester excellent flame retardancy, often results in loss of other properties of polyester, such as heat resistance, mechanical properties, etc. Therefore, how to prepare modified PET with high elastic modulus and good molding properties has always been a difficult point in the polyester field.

[0005] Due to the above reasons, it is urgent to study a composite polyester material with good mechanical properties and good thermal stability. Summary of the invention

[0006] In order to overcome the above problems, the inventors have conducted intensive research on polyester and its composites, and developed a composite polyester prepared by carbon dots and polyester. The doping of carbon dots gives polyester excellent mechanical properties and fluorescence, and has the potential to prepare fluorescent anti-counterfeiting fibers. The present invention adopts a blending or in-situ polymerization method to prepare the composite polyester. The carbon dots serve as crosslinking points in the polymerization system, which increases the amount of residual carbon in the system and reduces the rate of thermal weight loss. Since the carbon dots are highly compatible with polyester, they are conducive to improving the mechanical properties of the matrix polyester, providing a new development idea for the enhancement and modification of polyester, thereby completing the present invention.

[0007] Specifically, the purpose of the present invention is to provide the following aspects:

[0008] In a first aspect, a composite polyester is provided, wherein the composite polyester comprises carbon dots and polyester.

[0009] In a second aspect, a method for preparing a composite polyester is provided, wherein the polyester is melted, mixed with carbon dots, and solidified.

[0010] In a third aspect, a method for preparing a composite polyester is provided, wherein the carbon dots are dissolved in an alcohol compound and mixed evenly, and then mixed with a carboxylic acid compound to undergo esterification reaction and polycondensation reaction.

[0011] In a fourth aspect, use of the composite polyester described in the first aspect or the composite polyester prepared by the method described in the second aspect or the third aspect in the field of luminescent plastics.

[0012] The beneficial effects of the present invention include:

[0013] (1) According to the composite polyester provided by the present invention, the doping of carbon dots will give the polyester excellent mechanical properties and fluorescence, and has the potential to prepare fluorescent anti-counterfeiting fibers.

[0014] (2) According to the method for preparing composite polyester provided by the present invention, the composite polyester is prepared by blending or in-situ polymerization, and the carbon dots are used as crosslinking points in the polymerization system, so that the residual carbon content of the system is increased and the thermal weight loss rate is reduced.

[0015] (3) According to the method for preparing composite polyester provided by the present invention, carbon dots are highly compatible with polyester. The unique properties of carbon dots provide new development ideas for polyester enhancement and modification, and also guide new development directions for the field of luminescent plastics. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 TEM characterization of carbon dots prepared in Example 1 is shown;

[0017] Figure 2 The fluorescence spectrum of the carbon dots emitted from Example 1 is shown;

[0018] Figure 3 The infrared spectrum of carbon dots in Example 1 is shown;

[0019] Figure 4 The thermogravimetric change curve in Experimental Example 1 is shown;

[0020] Figure 5 The DSC curve in Experimental Example 2 is shown;

[0021] Figure 6 The cone calorimetry test curve in Experimental Example 3-3 is shown;

[0022] Figure 7 FTIR graphs of Experimental Examples 3-4 are shown;

[0023] Figure 8 The photographs in Experimental Examples 3-5 are shown;

[0024] Fig. 9 The photographs in Experimental Examples 3-5 are shown;

[0025] Fig.10 A comparison chart of tensile strength in Experimental Example 4 is shown. DETAILED DESCRIPTION

[0026] The present invention will be further described in detail below through the accompanying drawings and embodiments. Through these descriptions, the characteristics and advantages of the present invention will become more clear and distinct.

[0027] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.

[0028] A first aspect of the present invention is to provide a composite polyester comprising carbon dots and polyester.

[0029] From the earliest use of CNTs in polyester modification to the recent focus on graphene, the research on the preparation of composite polyester based on nanocarbon materials has only been carried out for more than 10 years, but it has shown great vitality and achieved encouraging results. Practice has shown that nanocarbon materials have obvious advantages in reducing the heat release rate and mass loss rate of polymers, showing good application prospects. However, although nanocarbon materials can significantly reduce the heat release rate and mass loss rate of materials, during the addition process, the mechanical properties of the prepared flame retardant will not be significantly improved due to easy agglomeration.

[0030] In addition, compared with traditional flame retardants, the current price of nanocarbon materials is still relatively high, and cost issues must also be considered when applying them to polyester modification.

[0031] In the present invention, the carbon dots have a small particle size, excellent thermal conductivity, mechanical properties and optical properties, as well as many advantages such as low cost, high fluorescence quantum yield, good stability and biocompatibility. It is a new type of nanocarbon material. Its excellent structure and properties determine that the carbon dots are easy to be compounded with polyester to realize its functionalization.

[0032] According to the present invention, the weight percentage of the carbon dots and the polyester is (0.01-20): (80.0-99.99), preferably (0.1-10): (92-99.5), and more preferably (0.5-5): (96-99).

[0033] Among them, due to excessive carbon points, the stress of the composite polyester is concentrated, resulting in a decrease in mechanical properties. Within the above range, the mechanical properties of the composite polyester are optimal and the fluorescence is strongest.

[0034] In the present invention, the particle size of the carbon dots is less than 20 nm, preferably 1 to 10 nm, and more preferably 5 to 7 nm. Small particle size carbon dots will enhance the compatibility of the carbon dots and the composite polyester, and also enhance the mechanical properties of the composite polyester.

[0035] According to the present invention, the excitation wavelength of the carbon dots is 200 to 500 nm, preferably 300 to 400 nm, and more preferably 320 to 360 nm.

[0036] According to a preferred embodiment, the carbon dots are prepared by a hydrothermal method, and the preparation method is simple, green and environmentally friendly.

[0037] Furthermore, gelatin is dissolved in water, reacted in an autoclave at a temperature of 100 to 300° C. for 6 to 48 hours, and then cooled, separated, and dried to obtain the product.

[0038] In the present invention, if the temperature for preparing carbon dots is too high, the carbon dots will agglomerate during the carbonization process of gelatin, resulting in a weakening of the fluorescence intensity. If the reaction time is too long, the fluorescence intensity of the carbon dots will be slightly affected. When the reaction temperature is 100-300°C and the reaction time is 6-48h, the obtained carbon dots have a small particle size, high fluorescence intensity and are evenly dispersed.

[0039] In a further preferred embodiment, gelatin is dissolved in water, reacted in an autoclave at a temperature of 180 to 260° C. for 12 to 36 hours, and then cooled, separated, and dried to obtain the product.

[0040] In a further preferred embodiment, gelatin is dissolved in water, reacted in an autoclave at a temperature of 210° C. for 36 hours, and then cooled, separated, and dried to obtain the product.

[0041] According to the present invention, the gelatin is commercially available, preferably commercially available industrial gelatin.

[0042] Among them, the raw materials of industrial gelatin are mostly tanned leather scraps, which are difficult to reuse due to the presence of heavy metals such as Cr(VI) and are discarded, causing environmental pollution. The carbon dots made from industrial gelatin have good effects and low costs, and can also promote resource utilization.

[0043] In the present invention, the polyester has good fluidity and adhesion, and is not limited to any commercially available polyester, including any one or more of polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), and polycarbonate (PC), preferably PET. Among them, the PET has the characteristics of high strength, stiffness, wear resistance, and good wearability.

[0044] According to the present invention, the polyester can also be prepared by reaction. Taking PET as an example, it can be prepared by reaction of an alcohol compound and a carboxylic acid compound under the action of a catalyst.

[0045] The alcohol compound includes monoalcohols and polyols, preferably polyols, such as ethylene glycol, glycerol, sorbitol, etc., more preferably ethylene glycol.

[0046] Among them, the polyester complex prepared from structurally symmetrical ethylene glycol has obvious crystallinity.

[0047] According to a preferred embodiment, the carboxylic acid compound includes aliphatic carboxylic acid and aromatic carboxylic acid, preferably aromatic carboxylic acid, such as terephthalic acid and 5-methyl-isophthalic acid, more preferably terephthalic acid, which is easy to be crystallized and purified.

[0048] According to the present invention, the catalyst plays an important role in the esterification and polycondensation stages of polyester and can accelerate the reaction rate. There are many types of compounds that have catalytic effects on the esterification and polycondensation reactions of polyester, almost covering all elements except halogen elements and inert elements. Antimony-based catalysts have moderate activity and low price, showing unique advantages in the polyester industry.

[0049] In the present invention, the antimony-based catalyst is preferably selected from any one or more of antimony acetate, antimony oxide, and ethylene glycol antimony. Considering factors such as catalyst performance and price, antimony oxide is more preferably used as the catalyst.

[0050] According to the present invention, the reaction includes an esterification reaction and a polycondensation reaction.

[0051] Wherein, the esterification reaction temperature is 200-300°C, preferably 210-250°C, and more preferably 220-230°C.

[0052] In the present invention, increasing the temperature increases the movement speed of the molecules, which can prompt the esterification reaction to quickly reach equilibrium, which is beneficial to the increase of the molecular weight of the polymer. However, the higher the temperature, the better. If the temperature is higher than 300°C, it will lead to decarboxylation of carboxylic acid and thermal cracking reaction of polyester molecules, resulting in poor quality of composite polyester.

[0053] In the present invention, since an excessively long esterification reaction time leads to a decrease in the conversion rate of the carboxylic acid compound, the reaction time is controlled to be 0.5 to 3 hours, preferably 1 to 2 hours, and more preferably 1.5 to 2.0 hours.

[0054] According to the present invention, before the polycondensation reaction, an antioxidant and an anti-hydrolysis agent are added to the reaction system. To ensure the complete esterification reaction, a small amount of alcohol compound is also added to the reaction system.

[0055] Among them, the main chain of polyester contains molecular chains or fatty chain segments. When melt processing or used at high temperatures, thermal oxidation reactions are prone to occur, which causes the polyester to turn yellow, gray, and its physical and mechanical properties to deteriorate or even be destroyed. The reason is that oxidative degradation reduces the molar mass of polyester. Antioxidants can inhibit the breakage of molecular chains or fatty chain segments and extend the performance of polyester materials.

[0056] According to the present invention, the antioxidant is selected from thioesters or phosphites, preferably phosphites, such as triphenyl phosphite, dioctadecyl pentaerythritol diphosphite, tris(nonylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, more preferably triphenyl phosphite.

[0057] In the present invention, the phosphite has good antioxidant effect and is a halogen-free and environmentally friendly antioxidant, especially triphenyl phosphite, which also has certain flame retardancy.

[0058] According to the present invention, in a humid and warm environment, water molecules will destroy the macromolecular chains of polyester, causing hydrolysis reaction, thereby causing its degradation. In order to effectively prevent the occurrence of hydrolysis, an anti-hydrolysis agent is added.

[0059] In the present invention, the anti-hydrolysis agent includes any one or more of carbodiimide, oxazoline compounds, and epoxy compounds, preferably epoxy compounds, such as anti-hydrolysis agent 1010.

[0060] In the present invention, the anti-hydrolysis agent 1010 has high activity and can effectively capture the carboxyl groups generated by polymer hydrolysis to prevent the further progress of the hydrolysis reaction, thereby effectively inhibiting the degradation of the mechanical properties of the polyester material caused by hydrolysis and greatly extending the service life of the product.

[0061] According to the present invention, in order to avoid the introduction of impurities, the type of the alcohol compound is preferably the same as the type of the alcohol compound added in the esterification reaction.

[0062] According to the present invention, the higher the temperature, the faster the reaction speed, but too high a temperature will cause the polymer to undergo thermal degradation. Preferably, the polycondensation reaction is first reacted at a relatively low temperature, and as the reaction proceeds, the viscosity of the material melt increases, and then the temperature is raised again, which is conducive to the diffusion and escape of the generated small molecular byproducts. The polycondensation reaction includes:

[0063] Low vacuum stage: reaction temperature is 200-300°C, reaction time is 0.2-8h, and system pressure is controlled at -80--150kPa;

[0064] High vacuum stage: reaction temperature is 200-400°C, reaction time is 1-12h, and system pressure is controlled at -70--120kPa.

[0065] In a further preferred embodiment, the polycondensation reaction comprises:

[0066] Low vacuum stage: reaction temperature is 230-280°C, reaction time is 0.4-2h, and system pressure is controlled at -90--110kPa;

[0067] High vacuum stage: reaction temperature is 250-300°C, reaction time is 2-5h, and system pressure is controlled at -90-100kPa.

[0068] In a further preferred embodiment, the polycondensation reaction comprises:

[0069] Low vacuum stage: reaction temperature is 265-268°C, reaction time is 0.8h, and system pressure is controlled at -98kPa;

[0070] High vacuum stage: reaction temperature is 284-287°C, reaction time is 2.5h, and system pressure is controlled at -95kPa.

[0071] According to the present invention, the weight ratio of the alcohol compound, the carboxylic acid compound, the catalyst, the antioxidant and the anti-hydrolysis agent is (350-600):(800-1300):(0.1-5):(0.1-3):1, preferably (400-500):(900-1100):(0.2-0.7):(0.5-2):1, and more preferably (440-450):(990-1000):(0.3-0.5):(0.8-1.1):1.

[0072] In the present invention, the doping of carbon dots improves the mechanical properties of the composite polyester and gives the composite polyester material fluorescence, which has very good application prospects in the field of plastics. Among them, the tensile strength of the composite polyester is above 25MPa, preferably above 40MPa, and more preferably above 50MPa; the elastic modulus of the composite polyester reaches above 550MPa, preferably above 600MPa, and more preferably above 700MPa; the elongation at break of the composite polyester reaches above 8%, preferably above 100%, more preferably above 700%, and even above 500%; the fluorescence intensity of the composite polyester can reach 6×10 4 Above, preferably 1×10 5 More preferably, 2×10 5 above.

[0073] According to a preferred embodiment, the composite polyester is prepared by blending carbon dots and polyester. Specifically, the polyester is melted, mixed with the carbon dots, and then solidified.

[0074] In the prior art, composite polyester is prepared by blending method without changing the polymerization production process of polyester. The method is flexible and easy to adjust. However, as a blending filler, it generally has poor compatibility with polyester, and the addition amount is usually high, which will cause the appearance and mechanical properties of the composite polyester to decrease. How to design the compound formula of composite polyester and overcome the compatibility and dispersibility problems caused by blending flame retardant modification are the current difficulties.

[0075] In the present invention, the composite polyester prepared by blending carbon dots with small particle size and excellent performance with polyester improves the mechanical properties of the composite polyester and gives the composite polyester fluorescence without changing the flame retardancy of the polyester itself. During blending, the amount of carbon dots added is extremely small, which is an ideal blending filler for preparing composite polyester.

[0076] In the present invention, the melting temperature of the polyester is 250 to 300°C, preferably 260 to 290°C, and more preferably 265 to 275°C.

[0077] According to the present invention, when the temperature reaches the melting point of polyester, the glass transition temperature of polyester, in order to improve the reliability and durability of the composite polyester, the fluidity of the polyester is best when the temperature is 250-300°C, and the obtained composite polyester has the best performance.

[0078] In the present invention, the melting time of the polyester is 0.1 to 1 h, preferably 0.2 to 0.5 h, and more preferably 0.2 to 0.3 h.

[0079] According to the present invention, when the polyester melting time is 0.1 to 1 h, it is beneficial for the polyester to melt completely, which is beneficial for increasing the contact area between the carbon dots and the molten polyester, and for evenly dispersing the carbon dots in the polyester, thereby avoiding uneven dispersion of the carbon dots leading to a decrease in stress of the obtained composite polyester.

[0080] In the present invention, stirring after mixing the carbon dots and the polyester is beneficial to fully mixing the carbon dots and the molten polyester, thereby improving the performance of the composite polyester. The stirring time is 0.1 to 5 hours, preferably 0.2 to 2 hours, and more preferably 0.5 to 1 hour.

[0081] In the present invention, the curing temperature is room temperature, such as 25°C.

[0082] According to the present invention, during the curing process, since the curing temperature is lower than the glass transition temperature of the polyester, the polyester cools too fast, providing a greater driving force for cooling crystallization, accelerating the movement of the molecular chain, and improving the crystallization performance of the composite polyester. According to another preferred embodiment, the composite polyester is prepared by in-situ copolymerization of carbon dots and polyester, specifically, by esterification and polycondensation of carbon dots and prepolymer monomers.

[0083] In the present invention, the prepolymer monomer includes an alcohol compound and a carboxylic acid compound.

[0084] According to a preferred embodiment, the alcohol compound includes monoalcohols and polyols, preferably polyols, such as ethylene glycol, glycerol, sorbitol, etc., more preferably ethylene glycol.

[0085] According to a preferred embodiment, the carboxylic acid compound includes aliphatic carboxylic acids and aromatic carboxylic acids, preferably aromatic carboxylic acids, such as terephthalic acid and 5-methyl-isophthalic acid, and more preferably terephthalic acid.

[0086] According to the present invention, the catalyst is preferably an antimony-based catalyst, such as any one or more of antimony acetate, antimony oxide, and ethylene glycol antimony, and antimony oxide is more preferred as the catalyst.

[0087] According to the present invention, the esterification temperature is 200-300° C., preferably 210-250° C., more preferably 220-230° C.; the reaction time is 0.5-3 h, preferably 1-2 h, more preferably 1.5-2.0 h.

[0088] According to the present invention, before the polycondensation reaction, an antioxidant, an anti-hydrolysis agent and a small amount of alcohol compounds are added to the reaction system.

[0089] According to the present invention, the antioxidant is selected from thioesters or phosphites, preferably phosphites, such as triphenyl phosphite, dioctadecyl pentaerythritol diphosphite, tris(nonylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, more preferably triphenyl phosphite.

[0090] In the present invention, the anti-hydrolysis agent includes any one or more of carbodiimide, oxazoline compounds, and epoxy compounds, preferably epoxy compounds, such as anti-hydrolysis agent 1010.

[0091] According to the present invention, the polycondensation reaction comprises:

[0092] Low vacuum stage: reaction temperature is 200-300°C, reaction time is 0.2-8h, and system pressure is controlled at -80--150kPa;

[0093] High vacuum stage: reaction temperature is 200-400°C, reaction time is 1-12h, and system pressure is controlled at -70--120kPa.

[0094] In a further preferred embodiment, the polycondensation reaction comprises:

[0095] Low vacuum stage: reaction temperature is 230-280°C, reaction time is 0.4-2h, and system pressure is controlled at -90--110kPa;

[0096] High vacuum stage: reaction temperature is 250-300°C, reaction time is 2-5h, and system pressure is controlled at -90-100kPa.

[0097] In a further preferred embodiment, the polycondensation reaction comprises:

[0098] Low vacuum stage: reaction temperature is 265-268°C, reaction time is 0.8h, and system pressure is controlled at -98kPa;

[0099] High vacuum stage: reaction temperature is 284-287°C, reaction time is 2.5h, and system pressure is controlled at -95kPa.

[0100] According to the present invention, when the composite polyester is prepared by in-situ copolymerization, the weight ratio of the carbon dots, alcohol compounds, carboxylic acid compounds, catalysts, antioxidants and anti-hydrolysis agents is (0.1-10): (350-600): (800-1300): (0.1-5): (0.1-3): 1, preferably (0.5-7): (400-500): (900-1100): (0.2-0.7): (0.5-2): 1, and more preferably (1-6): (440-450): (990-1000): (0.3-0.5): (0.8-1.1): 1.

[0101] The second aspect of the present invention is to provide a method for preparing a composite polyester, which is prepared by melting the polyester, mixing it with carbon dots, and solidifying it.

[0102] According to the present invention, in order to avoid bubbles in the composite polyester obtained after curing and reduce the mechanical properties of the composite polyester, it is preferred that the curing process is carried out in a vacuum environment.

[0103] In a preferred embodiment, PET and carbon dots are mixed evenly under anaerobic conditions, then melt-blended under anaerobic conditions at polyester melting temperature and a rotation speed of 20 to 80 rpm, and then extruded into water at room temperature, cooled and solidified to obtain composite PET.

[0104] The third aspect of the present invention is to provide a method for preparing a composite polyester, wherein the carbon dots are dissolved in an alcohol compound and mixed evenly, and then mixed with a carboxylic acid compound to undergo esterification reaction and polycondensation reaction.

[0105] According to the present invention, the reactants are added to the reaction system in a specific order, which effectively avoids the agglomeration of carbon dots, facilitates the full contact between the carbon dots and the reactants, and improves the mechanical properties and fluorescence of the composite polyester.

[0106] According to a preferred embodiment, during the esterification reaction, a catalyst is added therein, and after the esterification reaction is completed and before the polycondensation reaction, an antioxidant, an anti-hydrolysis agent and a small amount of alcohol compound are added to the reaction system.

[0107] The fourth aspect of the present invention aims to provide the use of the composite polyester as described in the first aspect or the composite polyester prepared by the method described in the second aspect or the third aspect in the field of luminescent plastics.

[0108] Example

[0109] The present invention is further described below through specific examples, but these examples are merely exemplary and do not constitute any limitation to the scope of protection of the present invention.

[0110] The sources of the reagents used in the following examples are as follows:

[0111]

[0112]

[0113] Example 1 Preparation of carbon dots

[0114] 1.0 g of gelatin was weighed and placed in a 100 mL clean beaker. 20 mL of deionized water was used as the solvent. The mixture was stirred evenly and transferred to a 50 mL polytetrafluoroethylene lined reactor. The reactor was then placed in a hot air oven and reacted at 210 °C for 36 h. The reactor was then cooled naturally, and carbon dots were obtained by centrifugation and freeze drying. The TEM morphology is shown in FIG. Figure 1 As shown in the figure, it can be seen that the carbon dots are spherical in structure, evenly dispersed and without agglomeration, and their particle size is 6-7nm. When the excitation light wavelengths of the prepared carbon dots are 280nm, 300nm, 320nm, 340nm, 360nm, 380nm, and 400nm, the fluorescence spectra of the emitted light are shown in the figure. Figure 2 As shown in the figure, the fluorescence emission of carbon dots is a typical excitation wavelength-dependent type, that is, the position of the fluorescence emission peak changes with the change of the excitation wavelength, and the corresponding fluorescence intensities are 4.4×10 5 , 6.8×10 5 9.0×10 5 , 8.6×10 5 , 6.2×10 5 4.2×10 5 , 2.6×10 5 .

[0115] The infrared spectrum of the obtained carbon dots is shown in Figure 3 As shown in the spectrum, the carbon dots are in the range of 2500-3000 cm -1 、1553cm -1 Characteristic peaks appeared nearby, including 2945cm -1 The table shows the saturated CH stretching vibration peak, 1553 cm -1 C=O stretching vibration peak, 1633cm -1 and 1110cm -1 The stretching vibrations of carbon dots are OH, C=O and CO, respectively, indicating that the carbon dots contain -COOH and -OH on the surface. This further proves that carbon dots can be added to polyester as chain links by blending or in-situ copolymerization.

[0116] Example 2 Preparation of composite PET

[0117] (1) 4.0 g of the carbon dots (CDs) prepared in Example 1 were dissolved in 282 mL of ethylene glycol (EG) to obtain an EG-CDs solution. 700 g of PTA, 0.28 g of Sb2O3 and the EG-CDs solution were added to a polymerization reactor and reacted at 225°C for 1.5 h to obtain the oligomer BHET.

[0118] (2) After the reaction of step (1) was completed, 0.7 g of anti-hydrolysis agent 1010, 0.6 mL of triphenyl phosphite and 13.5 mL of EG were added to the oligomer BHET, and then a polymerization reaction was carried out. The polymerization reaction conditions were as follows:

[0119] Low vacuum stage: reaction temperature is 265-268°C, reaction time is 0.8h, and system pressure is controlled at -98kPa;

[0120] High vacuum stage: reaction temperature is 284-287°C, reaction time is 2.5h, and system pressure is controlled at -95kPa.

[0121] After the reaction is completed, a composite PET is obtained, and the carbon point content in the composite PET is 0.5wt%.

[0122] Example 3 Preparation of composite PET

[0123] The composite PET was prepared in a similar manner to Example 2, except that:

[0124] The weight of the added carbon dots was 8.0 g, and the carbon dot content in the prepared composite PET was 1.0 wt%.

[0125] Example 4 Preparation of composite PET

[0126] The composite PET was prepared in a similar manner to Example 2, except that:

[0127] The weight of the added carbon dots was 16.0 g, and the carbon dot content in the prepared composite PET was 2.0 wt%.

[0128] Example 5 Preparation of composite PET

[0129] The composite PET was prepared in a similar manner to Example 2, except that:

[0130] The weight of the added carbon dots was 24.0 g, and the carbon dot content in the prepared composite PET was 3.0 wt%.

[0131] Example 6 Preparation of composite PET

[0132] (1) 282 mL of EG, 700 g of terephthalic acid (PTA), and 0.28 g of Sb2O3 were added to a polymerization reactor and reacted in a 245°C heat preservation environment for 1.5 h. Then, 0.7 g of anti-hydrolysis agent 1010, 0.6 mL of triphenyl phosphite, and 13.5 mL of EG were added to the reaction system and a polymerization reaction was carried out. The polymerization reaction conditions were the same as those in Example 1 to obtain PET.

[0133] (2) Take 500 g of the PET prepared in step (1) and 2.5 g of the carbon dots (CDs) prepared in Example 1, and mix them thoroughly under anaerobic conditions. Use a PolyOS twin-screw extruder produced by HAAKE, Germany, to react under anaerobic conditions at 265° C. and a rotation speed of 45 rpm, and extrude the blended material of PET and carbon dots from the outlet of the PolyOS twin-screw extruder into room temperature water at 240° C. to prepare a composite PET.

[0134] The carbon dot content in the prepared composite PET is 0.5wt%.

[0135] Example 7 Preparation of composite PET

[0136] The composite PET was prepared in a similar manner to Example 6, except that:

[0137] The weight of the added carbon dots was 8.0 g, and the carbon dot content in the prepared composite PET was 1.0 wt%.

[0138] Example 8 Preparation of composite PET

[0139] The composite PET was prepared in a similar manner to Example 6, except that:

[0140] The weight of the added carbon dots was 16.0 g, and the carbon dot content in the prepared composite PET was 2.0 wt%.

[0141] Example 9 Preparation of composite PET

[0142] The composite PET was prepared in a similar manner to Example 6, except that:

[0143] The weight of the added carbon dots was 24.0 g, and the carbon dot content in the prepared composite PET was 3.0 wt%.

[0144] Comparative Example

[0145] Comparative Example 1

[0146] The composite PET was prepared in a manner similar to step (1) of Example 6, except that no carbon dots were added.

[0147] Experimental example

[0148] Experimental Example 1 Thermal Stability Analysis

[0149] The composite PET obtained in the above examples 2-9 and comparative example 1 was tested using a 209F1 thermogravimetric analyzer. The test conditions were a nitrogen atmosphere, a temperature range of 30 to 800°C, and a heating rate of 10°C / min. The thermogravimetric change results were as follows: Figure 5 As shown, Figure 4 -a shows the variation curve of the residual carbon content of the composite PET prepared in Examples 2-5 and Comparative Example 1 as the temperature increases, 4-b shows the variation curve of the mass reduction rate of the composite PET prepared in Examples 2-5 and Comparative Example 1 as the temperature increases, Figure 4 -c shows the variation curve of the residual carbon content of the composite PET prepared in Examples 6-9 and Comparative Example 1 as the temperature increases, and 4-d shows the mass reduction variation curve of the composite PET prepared in Examples 6-9 and Comparative Example 1 as the temperature increases; accordingly, the test data are shown in Table 1:

[0150] Table 1 Thermogravimetric test results

[0151]

[0152]

[0153] Among them, T 5wt% (°C) is the temperature at which the composite PET loses 5% of its mass.

[0154] Combination Figure 4 As shown in Table 1, compared with Example 1, the initial decomposition temperature of Examples 2-5 increased by an average of 5-10°C, indicating an improvement in heat resistance. Further compared with Examples 6-9, the initial decomposition temperature increased, but the numerical range decreased, indicating that in-situ copolymerization is better than blending. The maximum thermal weight loss rate increased. Compared with Example 1, Examples 2-5 showed an increase in the thermal decomposition rate. Further compared with Examples 6-9, the numerical range of the maximum thermal weight loss rate decreased, indicating that the thermal decomposition rate of in-situ copolymerization is greater than the thermal decomposition rate of blending. The maximum thermal decomposition temperature of Comparative Example 1 and Examples 2-9 remained almost unchanged, indicating that the addition of carbon dots did not change the thermal degradation process of PET. The amount of residual carbon at 700°C increased, indicating that the addition of carbon dots contributed to the formation of a heat-insulating carbon layer.

[0155] Experimental Example 2 Thermal Performance Test

[0156] 6-8 mg of the composite PET obtained in Examples 2-9 and Comparative Example 1 were taken respectively, and a Q2000 differential scanning calorimeter was used, with nitrogen as the protective gas, and the test conditions were set to a pressure of 0.1 MPa, a temperature increase program from 30°C to 300°C, a temperature increase rate of 10°C / min, and a temperature decrease rate of 10°C / min. The measured composite PET DSC curve is as follows: Figure 5 The test data is shown in Table 2:

[0157] Table 2 DSC data

[0158]

[0159]

[0160] Depend on Figure 5 From the data analysis of ab and Table 2, it can be seen that in Comparative Example 1 and Examples 2-5, as the amount of carbon dots added increases, the cold crystallization temperature increases, because the carbon dots inhibit crystallization in the flame retardant copolymer; the hot crystallization temperature decreases, indicating that the addition of carbon dots changes the linear molecular structure of PET, the regularity of the molecular chain decreases, and its steric effect increases. The melting temperature increases, because the carbon dots produce cross-linking in the polyester chain, its molecular weight and viscosity increase, so its melting temperature increases.

[0161] Depend on Figure 5 From the data analysis of cd and Table 2, it can be seen that in Comparative Example 1 and Implementations 6-9, with the increase of the amount of carbon dots added, the cold crystallization temperature and the hot crystallization temperature both decrease. This is because when the carbon dots are blended into the flame-retardant PET, the carbon dots act as nucleating agents and are easy to form crystals.

[0162] Experimental Example 3 Flame retardant performance test

[0163] Experimental Example 3-1 Limiting Oxygen Index (LOI) Test

[0164] The composite PET obtained in Examples 2-9 and Comparative Example 1 was prepared into test specimens with a size of 80 mm × 6.5 mm × 3 mm using a Haake MiniJet micro-sample forming instrument. Referring to GB / T2406-93 "Plastic Combustion Performance Test Method Oxygen Index Method", the LOI value of the sample was measured using a Dynisco limiting oxygen index analyzer, and the calculation results of ΔLOI and flame retardant efficiency (EFF) are shown in Table 3:

[0165] Table 3 LOI test results

[0166]

[0167]

[0168] As shown in Table 3, after adding carbon dots, the LOI values ​​are all improved, indicating that adding carbon dots helps to improve the LOI value of flame-retardant polyester. The ΔLOI (%) value of Example 4 is 11, indicating that the composite PET prepared by adding 2% carbon dots in situ copolymerization has the best flame retardant effect and reaches the flame retardant grade. EFF refers to the effect of each amount of CDs added in the flame-retardant polyester. The experimental data show that the flame retardant effect of each carbon dot in the flame-retardant polyester in situ copolymerization of carbon dots is better than the flame retardant effect of blending.

[0169] Experimental Example 3-2 Vertical Burning (UL-94) Test

[0170] The composite PET obtained in Examples 2-9 and Comparative Example 1 was prepared into test specimens with a size of 130 mm × 13 mm × 3 mm using a Haake MiniJet micro-sample forming instrument. With reference to the test standard GB / T2408-2008 "Horizontal and vertical methods for testing the combustion performance of plastics", the vertical combustion performance of the composite PET was tested using a CZF-3 horizontal combustion tester produced by Nanjing Jiangning District Analytical Instrument Factory. The test results are shown in Table 4:

[0171] Table 4 UL-94 test results

[0172]

[0173]

[0174] As can be seen from Table 4, by comparing Examples 2-9 and Comparative Example 1, the experimental data show that the total combustion time is reduced, indicating that they all have the effect of promoting carbonization, among which Examples 2-5 are reduced by about 50%, and Example 4 has the best effect. For Examples 6-9, as the amount of carbon dots added increases, the total time is reduced, and Example 9 has the most significant effect.

[0175] Experimental Example 3-3 Cone Calorimetry (CONE) Test

[0176] The composite PET obtained in Examples 2-9 and Comparative Example 1 was prepared into test specimens with a size of 100 mm×100 mm×3 mm using a HaakeMiniJet micro-sample forming instrument. Referring to the test standard ISO 5660-1 "Reaction to fire test heat release, smoke production and mass loss rate Part 1: Heat release rate (cone calorimeter method)", the composite PET was tested using the British Fire Testing Technology Ltd standard cone calorimeter (FTT Standard Corn Calorimeter), and the parameter radiation power was set to 50KW / m 2 , Figure 6 Table 5 shows the cone calorimetry test results of the composite PET obtained in Examples 2-9 and Comparative Example 1.

[0177] Table 5 Cone calorimetry test results

[0178]

[0179]

[0180] Depend on Figure 6-aHRR shows that the heat release peak of the flame-retardant copolyester with carbon dots added is significantly reduced. Comparison of Example 1 with Implementation 2-5 shows that as the amount of carbon dots added increases, the heat release peak gradually decreases, decreasing by 38.27%, 55.51%, 56.47%, and 57.95%, respectively. Comparison of Example 1 with Implementation 6-9 shows that the heat release peaks are reduced to 52.05%, 52.24%, 50.58%, and 59.62%, respectively. In 6-bTHR, comparison of Example 1 with Implementation 2-5 shows that as the amount of carbon dots added increases, the total heat release gradually decreases, with Examples 4 and 5 decreasing by 13.92%. Comparison of Example 1 with Implementation 6-9 shows that as the amount of carbon dots added increases, the total heat release gradually decreases, with Example 9 decreasing by 29.11%. Figure 6 The same pattern also exists in the -cTSP graph.

[0181] Experimental Example 3-4 Residual Carbon Structure Characterization Test

[0182] The residual carbon structure of the composite PET prepared in Examples 2-9 and Comparative Example 1 was characterized by Fourier transform infrared spectroscopy (FTIR) with a scanning range of 4000-400 cm -1 ,like Figure 7 As shown, Figure 7 -a shows the FTIR characterization of the composite PET prepared in Examples 2-5 and Comparative Example 1, Figure 7 -b shows the FTIR characterization of the composite PET prepared in Examples 6-9 and Comparative Example 1.

[0183] Depend on Figure 7 -a shows the FTIR characterization results of the composite PET prepared in Examples 2-5 and Comparative Example 1. It can be seen that with the increase of the amount of carbon dots added, the 1100cm -1 The peak intensity is enhanced because CO is formed, which further forms COC, thereby forming a heat-insulating carbon layer and further improving the barrier capacity. Figure 7 -b shows that Examples 6-9 and Comparative Example 1 have the same results.

[0184] Experimental Example 3-5 Characterization of residual carbon morphology

[0185] The results were obtained using a JSM-6360 scanning electron microscope from JEOL Ltd. at a vacuum of 9.63×10 -3 Pa, the residual carbon morphology of the composite PET prepared in Examples 2-9 and Comparative Example 1 was observed under the condition of 8 kV voltage, wherein the scale of the SEM characterization image is 50 μm, and the obtained image is as follows Figure 8-9 As shown, Figure 8 The residual carbon morphology of Examples 2-5 and Comparative Example 1 is shown. Fig. 9 The residual carbon morphology characterization of Examples 6-9 and Comparative Example 1 is shown.

[0186] Specifically:

[0187] 8-a is a digital carbon residue image of the composite PET prepared in Comparative Example 1. It can be seen that the pores on the surface of the composite PET carbon layer are relatively large and the carbon layer is relatively loose. 8-b is a carbon residue image of the composite PET prepared in Comparative Example 1 taken by a scanning electron microscope at a magnification of 200 times. The image shows that it has more and larger pores, indicating that it is flammable. 8-c is a carbon residue height image of the composite PET prepared in Comparative Example 1. Its carbon residue height is 0, indicating that it has not formed an insulating carbon layer and is flammable.

[0188] Figure 8 -d is the digital carbon residue image of Example 2, 8-g is the digital carbon residue image of Example 3, 8-j is the digital carbon residue image of Example 4, and 8-m is the digital carbon residue image of Example 5. The images show that with the increase of the amount of carbon dots added, more glass-like non-porous and smooth carbon layers are formed on the surface, and the pore size of the porous part is smaller.

[0189] Figure 8 -e is the carbon residue image taken by scanning electron microscope at 200 times magnification in Example 2, Figure 8 -h is the carbon residue image taken by scanning electron microscope at 200 times magnification in Example 3, Figure 8 -k Example 4 is a carbon residue image taken by a scanning electron microscope at a magnification of 200 times, Figure 8 -n is the residual carbon image taken by scanning electron microscope at 200 times magnification in Example 5. The image shows that with the increase of the amount of carbon dots added, the pore size decreases, the number of pores decreases, and the number of unbroken bubbles increases.

[0190] Figure 8 -f is the residual carbon height of Example 2, Figure 8 -i is the residual carbon height of Example 3, Figure 8 -1 is the residual carbon height of Example 4, Figure 8 -o is the residual carbon height of Example 5. With the increase of the amount of carbon dots added, the carbon layer height gradually increases, which are 1.50cm, 2.50cm, 3.00cm, and 3.00cm respectively. The data show that with the increase of carbon dots, it is helpful to form a heat-insulating carbon layer.

[0191] Fig. 9 -a, 9-d, 9-g, 9-j, and 9-m correspond to the composite PET digital carbon residue images prepared in Example 1 and Example 6-9, respectively. Fig. 9 -b, 9-e, 9-h, 9-k, and 9-n correspond to the residual carbon images of the composite PET prepared in Example 1 and Example 6-9, which were taken by scanning electron microscope at a magnification of 200 times. Fig. 9-c, 9-f, 9-i, 9-l, and 9-o correspond to the carbon residue height pictures of the composite PET prepared in comparative example 1 and examples 6-9, respectively, and the conclusions of the carbon residue results of the composite PET prepared in examples 2-5 and comparative example 1 are the same.

[0192] Experimental Example 4 Mechanical Properties Test

[0193] Before testing, the composite PET prepared in Examples 2-9 and Comparative Example 1 was used to prepare dumbbell-shaped test specimens with a middle handle of 30 mm×4 mm×2 mm using a Haake MiniJet micro-sample forming instrument. The tensile strength, elastic modulus and elongation at break of the specimens were then tested using an electronic universal strength tester. The results are shown in Table 5:

[0194] Table 5 Mechanical properties test results

[0195]

[0196]

[0197] The corresponding tensile strength comparison is Fig.10 As shown, combined Fig.10 From Table 5, we can see that Fig.10 As shown in Table 5, the tensile strength of the composite PET prepared in Example 4 is significantly increased by about 10%, indicating that a certain amount of carbon dots added is helpful to improve the mechanical properties of PET, because the carbon dots form a cross-linked structure in the PET molecular structure. However, the tensile strength of the composite PET prepared in Examples 6-9 by blending is not as good as that of the composite PET prepared in Examples 2-5, because stress concentration is formed during the blending process due to uneven mixing.

[0198] The present invention is described in detail above in combination with preferred embodiments and exemplary examples. However, it should be noted that these specific embodiments are only illustrative explanations of the present invention and do not constitute any limitation on the protection scope of the present invention. Without exceeding the spirit and protection scope of the present invention, various improvements, equivalent substitutions or modifications may be made to the technical content of the present invention and its embodiments, which all fall within the protection scope of the present invention. The protection scope of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a composite polyester, characterized in that: The composite polyester comprises carbon dots and polyester, The weight percentage of the carbon dots and the polyester is (0.5-5): (96-99), Gelatin is dissolved in water, reacted in an autoclave at a temperature of 210 to 260° C. for 12 to 36 hours, and then cooled, separated, and dried to obtain the carbon dots, wherein the carbon dots have a particle size of 6 to 7 nm. The polyester is polyethylene terephthalate, The composite polyester is prepared by in-situ copolymerization of carbon dots and polyester, wherein the carbon dots are dissolved in an alcohol compound and mixed evenly, and then mixed with a carboxylic acid compound to undergo esterification reaction and polycondensation reaction. During the esterification reaction, a catalyst is added therein. After the esterification reaction is completed and before the polycondensation reaction, an antioxidant, an anti-hydrolysis agent and an alcohol compound are added to the reaction system. The alcohol compound is ethylene glycol, the carboxylic acid compound is terephthalic acid, the catalyst is antimony oxide, the esterification temperature is 220-230° C., and the reaction time is 1.5-2.0 h. The polycondensation reaction comprises: Low vacuum stage: reaction temperature is 265-268°C, reaction time is 0.4-2h, and system pressure is controlled at -90--110kPa; High vacuum stage: reaction temperature is 284-287°C, reaction time is 2-5h, and system pressure is controlled at -90-100kPa. The weight ratio of the alcohol compound, the carboxylic acid compound, the catalyst, the antioxidant and the anti-hydrolysis agent is (440-450):(990-1000):(0.3-0.5):(0.8-1.1):

1.

2. The method for preparing the composite polyester according to claim 1, characterized in that: The excitation wavelength of carbon dots is 200-500nm.

Citation Information

Patent Citations

  • Preparation method of CDs / TPU fluorescent nanocomposite

    CN109504368A

  • Carbon quantum dot-polymer composite material, and preparation method and application thereof

    CN110819097A